Mobile Banking Services Strategy For BRI Syariah Customers (BSI) Bengkulu - Santi, Deni Widya; Saputra, Iwan; Putri, Nurrahma; Yarmunida, Miti; Harpepen, Andi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
There are three issues studied in this final project, namely (1) knowing which services are available through immobile ibanking, (2) customer perceptions of the imobile ibanking application, (3) constraints in operating the immobile ibanking service. The purpose of this research is to build quality services in customer satisfaction. The author uses this type of field research (Field Research) with qualitative descriptive research methods, namely research conducted directly in the field, from the results of this study that customers are satisfied with the mobile banking application, making it easier for customers to make transactions in the mobile banking application, the data is collected in the mobile banking application. This research comes from primary and secondary data sources in the form of interviews and documentation related to mobile banking services. It is hoped that a stable inetwork i will be given to users of the imobile ibanking application so that they are able to enjoy the features of the imobile ibanking application service in any circumstances. which is made easy for iBRI iSyariah customers to share with the imobile banking application, which is in the form of various interesting features that can be utilized by BRI iSyariah customers. This can increase the number of ibank BRI Syariah customers. From the results of this study, it can be concluded that the imobile ibanking service for customers of iBRI isyariah iBengkulu, can download the download ID of the iplay application store isstore so that customers can use the features that are available i service imobile ibanking application Perception or it is very responsive to customer service ibanking, and iyang easy services. By overcoming the less unstable inetwork, the customer has a strong i-network operator, by updating the application on imobile banking.